1980
DOI: 10.1139/b80-167
|View full text |Cite
|
Sign up to set email alerts
|

Primary vascular patterns in root meristems of Pontederia cordata and their relevance to studies of root development

Abstract: There are several files of metaxylem cells in root apices of Pontederia cordata L., each considered to consist of a series of prospective vessels with their ends in contact. Two longitudinally adjacent vessels may be in the same file of cells produced by the root apex or in adjacent files. As the root grows, successive prospective vessels are added to the apical ends of most of the files but not all files are continued. Addition of prospective vessels appears to take place within the "quiescent centre" of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Roots in members of this family typically have three or four tiers of apical initials: a tier of rootcap initials (or calyptrogen), one or two tiers of ground meristem-protoderm initials (periblem-dermatogen), and a tier of procambium or stelar initials (plerome). This has been confirmed by Charlton (1980), although Lee (1958) argued that a three-tiered meristem with one layer of initials for the ground meristem-protoderm tip was characteristic of the Pontederiaceae, like Eichhornia, and that all other patterns represented nonmedian sections of the apex. In his study of vascular patterns in adventitious roots of P. cordata, Charlton (1980) described the origin and location of primary and secondary raphide cells in the outer portions of the ground meristem.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Roots in members of this family typically have three or four tiers of apical initials: a tier of rootcap initials (or calyptrogen), one or two tiers of ground meristem-protoderm initials (periblem-dermatogen), and a tier of procambium or stelar initials (plerome). This has been confirmed by Charlton (1980), although Lee (1958) argued that a three-tiered meristem with one layer of initials for the ground meristem-protoderm tip was characteristic of the Pontederiaceae, like Eichhornia, and that all other patterns represented nonmedian sections of the apex. In his study of vascular patterns in adventitious roots of P. cordata, Charlton (1980) described the origin and location of primary and secondary raphide cells in the outer portions of the ground meristem.…”
mentioning
confidence: 89%
“…This has been confirmed by Charlton (1980), although Lee (1958) argued that a three-tiered meristem with one layer of initials for the ground meristem-protoderm tip was characteristic of the Pontederiaceae, like Eichhornia, and that all other patterns represented nonmedian sections of the apex. In his study of vascular patterns in adventitious roots of P. cordata, Charlton (1980) described the origin and location of primary and secondary raphide cells in the outer portions of the ground meristem. He also found that a quiescent center extended ϳ70 m behind the junction between the rootcap and the ground meristem-protoderm tip.…”
mentioning
confidence: 89%
See 2 more Smart Citations